Le Shakespeare Québécois des Années 1990 - Gagnon, Chantal (Theatre Research in Canada / Recherches théâtrales au Canada, 2003)
Translation scholar Annie Brisset has demonstrated that between 1968 and 1988, Quebec translations of foreign plays were linked to the nationalist discourse. The present research tries to establish, with a case study, if the same statement applies to the 1990s. In order to do so, three Quebec translations of Shakespeare’s The Tempest have been studied: Michel Garneau’s (1989), Antonine Maillet’s (1998) and Normand Chaurette’s (1998). After having analysed the language, the versification and the paratext in each translation, and after having briefly discussed retranslation of Shakespeare’s plays in Quebec, the author concludes that nationalist ideas play an important part in these translations. However, the Quebec theatre institution has taken up the task and it struggles for its own cultural, economic and symbolic survival.